2011
DOI: 10.1097/inf.0b013e3182137e35
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Characteristics of Suspected Herpes Zoster in Vaccinated Children

Abstract: Varicella vaccination of children has decreased varicella disease incidence, but introduced the occurrence of herpes zoster (HZ) from vaccine-type virus. We identified 14 vaccinated children with suspected HZ and confirmed varicella virus by polymerase chain reaction in 6 cases. Two cases were due to vaccine-type virus. Serum varicella IgM and IgG were not useful for diagnosis of HZ among vaccinated children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 11 publications
1
24
0
3
Order By: Relevance
“…However, a decrease of shingles in vaccinated children seems plausible if natural infection is prevented by varicella vaccination and if virus strains of vaccine-type are less likely to reactivate than wild-type strains. 23,24 In our analysis we did not rely only on the comparison of mean incidences between pre-and post-vaccination time, but described trends and changes over the entire observation period more precisely. We found joinpoint regression as an adequate tool for the analysis of time trends and possible changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a decrease of shingles in vaccinated children seems plausible if natural infection is prevented by varicella vaccination and if virus strains of vaccine-type are less likely to reactivate than wild-type strains. 23,24 In our analysis we did not rely only on the comparison of mean incidences between pre-and post-vaccination time, but described trends and changes over the entire observation period more precisely. We found joinpoint regression as an adequate tool for the analysis of time trends and possible changes.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of the presence of high or rising titers of antibodies to VZV, although rarely used today, can also be helpful. [16][17][18] Due to unavailability of PCR we use serology for confi rmation, indicating past exposure. Acyclovir is the fi rst choice treatment for children and the suggested dose is 10 mg/kg every 8 hours for 7 days.…”
Section: Case Reportmentioning
confidence: 99%
“…Several studies have shown that the incidence of herpes zoster in both healthy and immunocompromised children who received varicella vaccine is less than that experienced by healthy and immunocompromised children who experienced natural varicella infection, respectively [12] [15]- [17]. The lower incidence may be related to a lower rate of reactivation of the attenuated vaccine strain of varicella-zoster virus and the lower rate of rash following vaccination compared with wild-type varicella [12].…”
Section: Epidemiologymentioning
confidence: 99%
“…The onset of disease may be heralded by pain within the dermatome and precedes the lesions by 48 to 72 hours [1] [12]. The pain is due to acute neuritis and is related to viral replication, inflammation, and cytokine production leading to neuronal destruction and increased sensitivity of pain receptors [20].…”
Section: Clinical Manifestationsmentioning
confidence: 99%